An outbreak of non-fatal mushroom poisoning with Omphalotus olearius among Syrian refugees in Izmir, Turkey. (2nd January 2016) - Bal, Alkan; Anil, Murat; Yilmaz, Ismail; Akata, Ilgaz; Atilla, Ozge Duman
Abstract: Outbreak of mushroom poisoning is uncommon in Izmir, Turkey. We report an outbreak of mushroom poisoning with Omphalotus olearius in Syrian refugees. Nineteen patients (median age: 7.8 year; age range: 2–52 years; 16 female, 3 male) were admitted to the adult and pediatric emergency departments of Tepecik Training and Research Hospital, Izmir, due to vomiting and abdominal pain within 2 h after eating mushrooms. Transaminase levels were moderately elevated only in one patient. The symptoms disappeared in 8 h after admission. We present 19 Syrian refugees poisoning with O. olearius mushroom because of its rarity. In our opinion, this outbreak was a good example that how refugees can change the disease profile in emergency practice.